INCIDENCE OF POSTOPERATIVE THROMBOCYTOPENIA IN CORONARY ARTERY BYPASS GRAFT PATIENTS AND ITS OUTCOMES (Journal of Medical & Health Sciences Review, 2025)
Aim: To determine the incidence of postoperative thrombocytopenia in coronary artery bypass graft patients and its outcomesMethodology: This prospective study was conducted in in Department of Cardiac Surgery, National Institute of Cardiovascular Diseases, Karachi, Pakistan from Jan 2025 to Jun 2025. All admitted patients for CABG, both genders categorized as ASA type 1,2 & 3, having age 40 to 80 years were included in the study. Patients having thrombocytopenia before CABG surgery, with septicaemia after CABG surgery (secondary infection), with multi organ failure after CABG surgery, with drug induced thrombocytopenia before CABG surgery and with bone marrow suppression before CABG surgery were excluded from the study. Postoperatively each patient was evaluated for any haemorrhage, MI, stroke, acute kidney disease (AKI) and respiratory distress on daily basis till 30th day postoperatively. Microsoft excel was used for data analysis.Results: Out of 310 patients who undergone CABG males were 48.4% and females were 51.6%. The mean age of them being 59.2±9.25 years. Incidence of thrombocytopenia was 16.1% with female predominance. Thrombocytopenia was significantly associated with female gender. It was not associated with BMI, duration of disease. Significant outcomes of thrombocytopenia were acute kidney disease and stroke.Conclusion: The result of this study reveals that post CABG patients with postoperative thrombocytopenia are having increased risk of developing acute kidney disease, bleeding tendency, mortality and chances of stroke. Further studies are needed for validation of these results while utilizing data from other medical centres. Research into the possible mechanism of postoperative thrombocytopenia and how it will possibly relate to adverse outcomes should be undertaken.